Dziś, gdy na Ziemi Lubuskiej dyskryminuje się naszą kresową przeszłość, warto o naszych przodkach mówić, pisać i przypominać. Unikatowe fotografie i dokumenty ze zbiorów lubuskich kresowian w cyfrowym portalu archiwumkresowe.pl = Today, when the memory of the former polish eastern Borderlands (Kresy) is neglected, it is worth speaking and writing about our ancestors. Unique photographs and documents from the collections of people displaced from the Kresy and their descendants are now available online at archiwumkresowe.pl - Mykietów, Bogusław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The decision to establish the Kresy Muzeum in Lublin, and not in the west of the country, sparked a discussion among Lubusz Voivodeship enthusiasts of the topic. They blame institutions appointed to reasearch and popularise history for ignoring the origins of the present inhabitants of Lubusz Voivodeship, half of whom are descentants of the Kresy (more than in any other voivodeship).
Keywords: Polish; Eastern Borderlands; descendants; museum; archive; Lubusz Voivodeship; ancestors; Kresy; Polska; muzeum; archiwum; województwo lubuskie; przodkowie